Dapiglutide, a novel dual GLP‐1 and GLP‐2 receptor agonist, attenuates intestinal insufficiency in a murine model of short bowel. Issue 5 (18th November 2021) - Reiner, Johannes; Berlin, Peggy; Held, Jascha; Thiery, Johanna; Skarbaliene, Jolanta; Griffin, Jonathan; Russell, Wayne; Eriksson, Per‐Olof; Berner‐Hansen, Mark; Ehlers, Luise; Vollmar, Brigitte; Jaster, Robert; et al.
Abstract: Background: Extensive intestinal resection may lead to short bowel (SB) syndrome, resulting in intestinal insufficiency or intestinal failure (IF). Intestinal insufficiency and IF involve deficiency of the proglucagon‐derived hormones glucagon‐like peptide‐1 (GLP‐1) and GLP‐2. Two major problems of SB are epithelial surface loss and accelerated transit. Standard treatment now targets intestinal adaptation with a GLP‐2 analogue to enlarge absorptive surface area. It is possible that additional benefit can be gained from a combination of GLP‐1 and GLP‐2 activity, with the aim to enlarge intestinal surface area and slow intestinal transit. Methods: The GLP‐1– and GLP‐2–specific effects of the novel dual GLP‐1 receptor (GLP‐1R) and GLP‐2 receptor (GLP‐2R) agonist dapiglutide (rINN) were characterized in rodents. Furthermore, in a murine SB model of intestinal insufficiency with 40% ileocecal resection, the influence of dapiglutide on intestinal growth, body weight, food intake, volume status, and stool water content was tested against vehicle and sham‐operated male mice. Results: Dapiglutide significantly improves oral glucose tolerance, reduces intestinal transit time, and promotes intestinal growth. In the SB mouse model, dapiglutide promotes body weight recovery, despite unchanged intake of liquid diet. Dapiglutide promotes significant intestinal growth, as indicated by significantly increased villus height as well as intestinal length. Furthermore, dapiglutide reduces stool water losses, resulting in reduced plasma aldosterone. Conclusion: Dapiglutide possesses specific and potent GLP‐1R and GLP‐2R agonist effects in rodents. In the murine SB model, combined unimolecular GLP‐1R and GLP‐2R stimulation with dapiglutide potently attenuates intestinal insufficiency and potentially also IF.